Rapid determination of aminotris(methylenephosphonic acid) in water by ultraviolet photooxidation. Issue 4 (4th July 2017) - Zhang, Xiaoyun; Guo, Wenya; Zheng, Ying; Cheng, Zhongfa; Qi, Xiaojing; Gao, Canzhu
ABSTRACT: Aminotris(methylenephosphonic acid) is a commonly used reagent in circulating water to minimize deposit and corrosion inhibition that should be monitored. Aminotris(methylenephosphonic acid) was determined in circulating water using a photooxidation reaction to produce orthophosphate that was subsequently determined. The optimal conditions for analytical measurements were 1.0 g/L sodium persulfate oxidizing agent and a digestion time of 8 min. It was not necessary to control the pH. The optimum digestion efficiency of aminotris(methylenephosphonic acid) was 95% with good accuracy and precision and recoveries between 98% and 105%. The reported protocol is simple, rapid, and allows the on-line monitoring of aminotris(methylenephosphonic acid) in circulating water.